Redefining Leadership And Gender: The Concepts Of The “Female Leader” And The “Modern Woman” In Contemporary Uzbekistan - Khalikulova Khulkar Yuldashevna (International Journal Of History And Political Sciences, 2025)
This article explores the growing role of women in global and Uzbek society, emphasizing their increasing participation in leadership positions. The study analyzes historical and modern leadership theories, including masculine and feminine models, charismatic and authoritarian leadership, and the emerging concept of the “super-leader.” Special attention is given to the specific features of female leadership, such as empathy, cooperation, and emotional intelligence, which distinguish women leaders in the modern context. The findings reveal that in Uzbekistan, women leaders not only embody the qualities of traditional leadership but also integrate distinctive feminine skills, contributing significantly to both organizational efficiency and societal development. The study argues that recognizing and strengthening women’s leadership capacities is essential for advancing gender equality and accelerating socio-economic progress.